The use of bioabsorbable poly-L-lactide acid miniplate and screw (FIXSORB®-MX) for bone fixation in mandibular fracture: cases report - Tsuakasa Tsuji; Hideaki Kitada; Sinnosuke Abe (Journal of Dentomaxillofacial Science, 2018)
Objective: This report aims to elucidate the degree of degradation of bioabsorbable poly-L-lactide acid (PLLA) devices and the influence of these materials on the surrounding tissues in the human body.Methods: Two patients with fractured mandibles underwent treatment using a biodegradable fixation system.Â  In the first case, the plates and screws were removed along with extraction of an impacted wisdom tooth at 6 months after surgery, and in the second case, the same procedure was performed 12 months after surgery. Changes in the physical properties of the materials and histologic alterations in the periosteum and bone associated with the bioabsorbable plates were assessed.Results: The materials demonstrated adequate degradation in the human body, and skeletal stability proved sufficient for the duration of mandibular bone healing without complications after surgery.Conclusion: On the basis these findings, it can be concluded that PLLA implants are useful for the fixation of human mandibular fractures.